Pandangan Iqbal tentang Materi, Ruang, dan Waktu - Sudaryanto Sudaryanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
The concep of matter as a material thing atom or steady particle in time and space was replaced by relative theory with concept of matter as events system. The theory of modern physics has exchanged the meaning of